Efficacy of Clopidogrel and Clinical Outcome When Clopidogrel Is Coadministered With Atorvastatin and Lansoprazole: A Prospective, Randomized, Controlled Trial. Issue 50 (December 2015) - Zhang, Jian-rong; Wang, Di-qing; Du, Jun; Qu, Guang-su; Du, Jian-lin; Deng, Song-bai; Liu, Ya-jie; Cai, Jin-xi; She, Qiang
Abstract : Abstract: This prospective, randomized, nonblind, controlled trial evaluated the effects of clopidogrel on platelet function upon coadministration with atorvastatin and lansoprazole. One hundred four adult patients with non-ST-segment elevated acute coronary syndrome (NSTE-ACS) who underwent percutaneous coronary intervention (PCI) with drug-eluting stent implantation were included. All patients were treated with standard dual antiplatelet therapy (DAPT) plus rosuvastatin 10 mg daily after the operation. On the sixth day after PCI, patients were randomly divided into 4 groups, Group A: DAPT + atorvastatin 20 mg daily (a change from rosuvastatin to atorvastatin) + lansoprazole 30 mg daily, Group B: DAPT + atorvastatin 20 mg daily (a change from rosuvastatin to atorvastatin), Group C: DAPT + lansoprazole 30 mg daily (continuing to take rosuvastatin), Group D is the control group. Additional drugs were used according to the situation of patients. Platelet function and concentrations of platelet activation markers (granular membrane protein 140 (P-selectin), thromboxane B2 (TXB2), and human soluble cluster of differentiation 40 ligand (sCD40L)) were assessed before randomization and at 15- and 30-day follow-up visits. All patients were maintained on treatment for 6 months and observed for bleeding and ischemic events. A total of 104 patients were enrolled, 27 patients in group A, 26 patients in Group B/C, 25 patients in Group D separately, and all the patients were analyzed. There were no differences in platelet function and the levels of platelet activation markers (P-selectin, TXB2, and sCD40L) among or within the 4 groups at the 3 time points of interest ( P  > 0.05). In the subsequent 6 months, no significant bleeding events occurred, and 12 patients experienced ischemic events, these results were also not significantly different among the groups ( P  > 0.05). In patients diagnosed with NSTE-ACS who have had drug-eluting stent implantation, simultaneously administering clopidogrel, atorvastatin, and lansoprazole did not decrease the antiplatelet efficacy of clopidogrel or increase adverse event frequency over 6 months.